Kekuatan Hukum Surat Wasiat dalam Pewarisan pada Masyarakat Hukum Adat Bali - Hilda Batohir; I Gusti Ayu Kartika Wijayanti Sasmita (Jurnal Hukum Lex Generalis, 2025)
Under Balinese customary law, inheritance is based on a patrilineal system (kepurusa), in which inheritance rights are generally granted to male descendants, while daughters who marry out (ninggal kedaton) lose their status as heirs. In practice, however, wills particularly those executed before a notary are often employed to distribute inheritance to parties who, under customary norms, no longer possess inheritance rights. This creates normative issues regarding the legal status and binding force of wills, as their substance frequently conflicts with the principles of Balinese customary inheritance law. This study aims to examine, from a normative perspective, the position of wills in Balinese customary inheritance law and their implications for justice and legal certainty within the customary community.